Multi-objective Analysis of Sustainable Generation Expansion Planning based on Renewable Energy Potential: A case study of Bali Province of Indonesia - Al Hasibi, Rahmat Adiprasetya (International Journal of Sustainable Energy Planning and Management, 2021)
This article analyzes the role of renewable energy in producing sustainable generation expansion planning. The generation expansion planning is carried out using an optimization model which has two objective functions, namely the objective function of planning costs and the objective function of emissions. Multi-objective analysis was performed using the epsilon constraint method to produce the Pareto set. Solution points are selected from the Pareto set generated using the fuzzy decision making method. The process of determining the best solution points is based on three scenarios. Furthermore, calculations were carried out to obtain 7 indicators of sustainability covering economic, social, and environmental aspects. The sustainability index is calculated based on several predetermined policy options. The model is implemented using data obtained from the electricity system in Bali Province, Indonesia. From the analysis, the planning scenario by implementing renewable energy sources in the generation of electrical energy, namely scenario 3, results in an increase in the sustainability index with the highest value during the planning period. However, scenario 3 produces two sustainability indices from the economic aspect, namely the unit cost of generation and shared electricity cost to GDP, which is the lowest when compared to other scenarios.